Etiology, Clinical Assessment, and Surgical Repair of Plantar Plate Tears - Nery, Caio; Umans, Hilary; Baumfeld, Daniel (Seminars in Musculoskeletal Radiology, 2016)
The plantar plate has recently gained more attention as an important structure contributing to lesser metatarsophalangeal joint stability. This has prompted a significant growth of interest in the anatomy and biomechanics of the plantar plate and in the diagnosis and treatment of its injuries. Improved understanding of plantar plate function and predictable patterns of degeneration and failure has led to the development of a clinical staging and surgical grading system of plantar plate lesions. Relatively recent innovations allow the surgeon to access and repair plantar plate tears directly with reinsertion onto the base of the proximal phalanx. The addition of direct plantar plate repair represents a significant advance in the surgical restoration of alignment and functional stability of the lesser metatarsophalangeal joint.
Keywords: plantar plate; plantar plate tears; lesser toes deformities; metatarsophalangeal joint instability; plantar plate anatomy; treatment